Pengembangan Variasi Model Latihan Otot Tungkai Menggunakan Metode Latihan Plyometric untuk Atlet Sepak Bola U-12 Academy Football Arema - Muchamad Fahru Rochman Hidayatullah; Roesdiyanto Roesdiyanto; Kurniati Rahayuni (LPPM Politeknik Pratama, 2024)
This study aims to develop a plyometric exercise model to increase leg muscle strength in Academy Football Arema aged 12 years. In this study using research and development methods from Sugiyono with a procedural model. The subjects used in this study were 30 Academy Football Arema players aged 12 years. Instruments when analyzing data needs using questionnaires and interviews. The analytical technique used is quantitative analysis techniques. This research went through the validation test phase from several experts. The recapitulation results from soccer experts get scores with a percentage of 94%, coaching experts 94%, and 97%. Based on the results of expert validation, it is stated that the product of developing a plyometric exercise model to increase leg muscles at Academy Football Arema is very valid and is suitable for use at Academy Football Arema.